PENGARUH HUMAN DEVELOPMENT INDEX (HDI) DAN TINGKAT PENGANGGURAN TERBUKA (TPT) TERHADAP POVERTY GAP INDEX-P1 - Indriyani, Dwita; Nugroho, Wahyu; Sudjianto, Agus Eko (Universitas Nusa Cendana, 2024)
Poverty is a vicious cycle that is difficult to break and very complex, especially in developing countries. To overcome the problem of poverty, research is needed to find out the factors that influence it. This study aims to determine the effect of the Human Development Index (HDI) and the Open Unemployment Rate (TPT) on the Poverty Gap Index-P1. This research is a quantitative research using secondary data collected through the website of the Central Bureau of Statistics (BPS) of East Java and synchronized with the BPS of the city districts in the Karesidenan Kediri which are the research locations. The statistical test used is panel data regression with the Ordinary Least Square (OLS) method which has cross section and time series data characteristics. The results of this study show that the Human Development Index (HDI) and the Open Unemployment Rate (TPT) have a negative or insignificant relationship with the Poverty Depth Index-P1, both partially and simultaneously. This is indicated to be due to differences in geographical, economic, and human resource quality conditions in the ex-municipal districts in the Kediri Prefecture. Keywords: Human Development Index; Open Unemployment Rate, Poverty Gap Index-P1; Panel Data Regression